Analisis Fixed Assets Turn Over dalam Mengukur Tingkat Profitibilitas Perusahaan pada PT. Sampoerna Agro Tbk yang Terdaftar di BEI Periode 2013 - 2017 - Febriani, Selvy; Norisanti, Nor; Jhoansyah, Dicky (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2019)
The purpose of this study was to determine how much influence the fixed assets turn over in measuring the level of profitability at PT. Sampoerna Agro Tbk, which is listed on the Indonesia Stock Exchange (IDX) for the period 2013-2017 with data analysis using fixed assets turn over (FATO) and return on assets (ROA). This study uses a quantitative descriptive method with data collection methods using secondary data, namely library research and financial report documentation from PT. Sampoerna Agro Tbk, which is listed on the Indonesia Stock Exchange (IDX) from the period 2013 - 2017. The results of this study indicate the occurrence of fluctuations in income (ROA) at PT. Sampoerna Agro Tbk. And experiencing an increase in (FATO) therefore PT. Sampoerna Agro Tbk in processing assets owned is not optimal to generate sales. So that between income and fixed assets turn over is not balanced at PT. Sampoerna Agro Tbk in the period 2013-2017.